The Influence of Perceived Ease of Use and Service Quality on Purchase Decision Through Trust: Study on Grab Food Service Users in Central Java - R.R Endang Sutrasmawati; Dodi Slamet Rahaji (Management Analysis Journal, 2022)
This study aims to determine the effect of perceived ease of use and service quality on purchase decisions with trust as the intervening variable. The sampling technique used was nonprobability sampling, namely purposive sampling with a total sample of 100 respondents . The data analysis technique used in this study is Partial Least Square – Structural Equation Modeling (PLS-SEM) analysis. This analysis technique can determine the simultaneous linear relationship between research variables and latent variables. The results showed that perceived ease of use has a significant positive effect on purchase decisions. However, service quality has no significant positive effect on purchase decision. The variables perceived ease of use and service quality have a significant positive effect on trust. Then, the trust variable can positively and significantly mediate perceived of use and service quality on purchase decisions.